20/40 or Better Visual Acuity After Optic Neuritis: Not as Good as We Once Thought?. Issue 4 (December 2016) - Sabadia, Sakinah B.; Nolan, Rachel C.; Galetta, Kristin M.; Narayana, Kannan M.; Wilson, James A.; Calabresi, Peter A.; Frohman, Elliot M.; Galetta, Steven L.; Balcer, Laura J.
Abstract : Background: Although patients with acute optic neuritis (ON) recover high-contrast visual acuity (HCVA) to 20/40 or better in 95% of affected eyes, patients with a history of ON continue to note subjective abnormalities of vision. Furthermore, substantial and permanent thinning of the retinal nerve fiber layer (RNFL) and the ganglion cell layer (GCL) is now known to occur early in the course of ON. We measured vision-specific quality of life (QOL) in patients with a history of acute ON and recovery of VA to 20/40 or better in their affected eyes to determine how these QOL scores relate to RNFL and GCL thickness and low-contrast letter acuity (LCLA) across the spectrum of visual recovery. Methods: Data from an ongoing collaborative study of visual outcomes in multiple sclerosis and ON were analyzed for this cross-sectional observational cohort. Patients and disease-free control participants completed the 25-Item National Eye Institute Visual Functioning Questionnaire (NEI-VFQ-25) and 10-Item Neuro-Ophthalmic Supplement to the NEI-VFQ-25, as well as VA and LCLA testing for each eye separately and binocularly. Optical coherence tomography measures for each eye included peripapillary RNFL thickness and macular GCL + inner plexiform layer (GCL + IPL) thickness. Results: Patients with a history of acute ON and recovery to 20/40 or better VA (n = 113) had significantly reduced scores for the NEI-VFQ-25 (83.7 ± 15.4) and 10-Item Neuro-Ophthalmic Supplement (74.6 ± 17.4) compared with disease-free controls (98.2 ± 2.1 and 96.4 ± 5.2, P < 0.001, linear regression models, accounting for age and within-patient, intereye correlations). Most patients with 20/40 or better visual recovery (98/112, 88%) had monocular HCVA in their affected eye of 20/20 or better. Although patients with 20/50 or worse HCVA recovery demonstrated the worst performance on low-contrast acuity, affected eye RNFL and GCL + IPL thickness, and QOL scales, these measures were also significantly reduced among those with 20/40 or better HCVA recovery compared with controls. Conclusions: Patients with a history of ON and "good" visual recovery, defined in the literature as 20/40 or better HCVA, are left with clinically meaningful reductions in vision-specific QOL. Such patient-observed deficits reflect the underlying significant degrees of retinal axonal and neuronal loss and visual dysfunction that are now known to characterize ON even in the setting of maximal HCVA recovery. There remains an unmet therapeutic need for patients with ON.